MAIN NEONATAL HARMS ASSOCIATED WITH CESAREAN: A INTEGRATIVE REVIEW - Pablo Emanoel Damasceno Alves da Silva; Ian Mendonça Dantas de Matos; Samyra Maria Fontes de Sousa; João Gabriel Jacinto; Fabiana de Andrade Bringel (Revista de Patologia do Tocantins, 2025)
Introduction :The Cesarean Section is a medical procedure widely utilized. Originally, it was conceived as a last-resort intervention to save the life of the mother or fetus in critical situations. Over the years, however, it has become an increasingly common option, often favored by pregnant individuals given the perception of safety at the final stages of pregnancy. Factors such as maternal comorbidities, financial incentives and the lack of birth plans during prenatal care contribute significantly to the increase of CS rates. Nonetheless, this growing preference is not without its adverse impacts. Goals: To analyze the main neonatal harms associated with Cesarean Section.Methodology: This study comprehends an integrative review of the literature, utilizing the PubMed/Medline database and articles repositories (PUC-Goiás and E-Acadêmia). The research was conducted using the boolean operator “AND” and the keywords: “Cesarean Section”, “Infant”, “Newborn” and “Neonatology”. Five articles were selected for full reading, according to inclusion and exclusion criteria – articles published over the past six years and related to the subject, excluding incomplete or duplicated articles.Results: Studies indicate that Cesarean Section is associated with neonatal harms, such as respiratory problems, increased risk of infections, immunological disorders and possible impacts on neurological development. Vaginal delivery promotes the perinatal stress that stimulates pulmonary maturation through increased production of catecholamines and cortisol, processes absent in CS. Babies born by Cesarean Section are colonized by hospital bacteria, impairing immunological development. The correlation between the type of delivery and neurological disorders is yet inconclusive. Beyond that, CS is related with reduced skin-to-skin contact and reduced initial breastfeeding.Discussion: Despite necessary in several cases, CS presents substantial risks to the newborn. The respiratory complications result from the lack of physiological stress of vaginal delivery, which is essential to extrauterine respiratory adaptation. Bacterial colonization in CS can impair the immune system, increasing vulnerability to infections and allergies. Reduced skin-to-skin contact and lack of early breastfeeding can also impact the bond between mother-baby and neonatal health, increasing the need for neonatal interventions. Conclusion: Based on the information analyzed, it is evident that the Cesarean Section, despite being a common practice, is associated with an increase in risk of neonatal complications. The sanitary interventions must be focused on raising awareness of the risks involved and promoting policies that ensure informed choice and appropriate use of this practice. KEYWORDS: Cesarean Section; Newborn; Infant; Neonatology;